(untitled) (Research, Society and Development, 2026)
Objective: To evaluate the crystalline phase composition and antimicrobial activity of white Portland cement modified with silver nanoparticles (WPC + NPs-Ag) compared with White Mineral Trioxide Aggregate (WMTA) and Biodentine®. Methods: An in vitro experimental study was conducted. Crystalline phase characterization was performed using X-ray diffraction (XRD), with quantification through the Rietveld refinement method. Antimicrobial activity was evaluated using the agar diffusion technique against Enterococcus faecalis ATCC 29212 and Candida albicans ATCC 90028 after 24 and 48 hours of incubation at 37 °C. Statistical analysis was performed using one-way ANOVA followed by Bonferroni post hoc test (p < 0.05). Results: WPC + NPs-Ag showed a crystalline composition similar to that observed in WMTA and Biodentine®, with predominance of calcium silicate phases and the presence of metallic silver, without relevant alterations in the cementitious matrix. From a microbiological perspective, the experimental material exhibited significantly larger inhibition zones against E. faecalis and C. albicans compared with WMTA and Biodentine® (p < 0.05). Conclusion: The incorporation of silver nanoparticles into white Portland cement enhances its antimicrobial activity without significantly modifying its crystalline structure, suggesting its potential as an alternative experimental material for endodontic applications. However, further studies are required to confirm its biocompatibility and clinical performance.